Learning Qira'ah Al-Qur'an Imam Nafi' History of Qolun at MTs Ar – Ridha - Achyar Zein; Salminawati Salminawati; Dedek Husairi (Budapest International Research and Critics University, 2022)
This study deals with Learning Qira'ah Al-Qur'an Imam Nafi' History of Qolun at MTs Ar – Ridha. This study used descriptive qualitative. The purpose of a method used is to obtain the effectiveness of the use of the method itself. The effectiveness of the method can be seen from the feelings of students who are happy and happy in participating in learning so that student interest and attention arises in participating in the learning. It can be concluded that the planning of this Qira'ah program already has a sharp thought and is really mature. The implementation of learning that is practiced by the teacher and mentor of Qira'ah Al-Qur'an Imam Nafi' History of Qolun MTS AR-RIDHA has a very good concept and format. The evaluation carried out by the Qira'ah Al-Qur'an teachers Imam Nafi' History of Qolun at MTS AR-RIDHA has included several survaluations